Glacial tragedy - Yu. V. Efremov (Лëд и снег, 2016)
Review on the book written by V.M. Kotlyakov, O.V. Rototaeva, G.A. Nosenko, L.V. Desinov, N.I. Osokin, R.A. Chernov «Karmadon catastrophe: what happened and what we should wait for in future». Мoscow: Publishing House «Kodeks», 2014. 184 p.